PERANCANGAN SISTEM INFORMASI JUAL BELI PROPERTI MENGGUNAKAN CHAT BOT TELEGRAM YANG TERINTEGRASI DENGAN WEB MENGGUNAKAN METODE PROTOTYPE - Eko Febriansyah; Endar Nirmala (Journal of Research and Publication Innovation, 2023)
Buying and selling activities in the community is an activity that is usually carried out at any time by humans, as well as buying and selling in the property sector. One of the things that is in the spotlight is how a seller markets his goods through conventional advertisements such as banners, banners and so on, and in my opinion it costs too much. As for the buyer, it is less effective if the buyer wants to know information on the property being sold, because usually the information listed in the banner is very limited, and if you want to contact the owner directly, the owner certainly cannot be contacted for 24 hours. Therefore we need a system that can overcome these problems from the seller's side and from the buyer's side, that is a chatbot. Where this chatbot can reduce advertising costs because there is no need to print a banner and the like. From the buyer side, they can find out more complete information on the property and can access that information at any time. The chatbot runs using the Telegram application.